Clinical pathological and epidemiological study of triple negative breast cancer - Ajay, Arun; Radhakrishnan, Priya (International Journal of Research in Medical Sciences, 2017)
Background: Worldwide breast cancer is the most frequently diagnosed life threatening cancer in women and a leading cause of cancer death among women. In Kerala, India around 30% of cancer-affected women have carcinoma breast. Breast carcinomas which do not express estrogen (ER), progesterone (PR), and human epidermal growth factor receptor 2 (HER-2/neu) receptors are known as triple negative breast carcinomas (TNBC). They are extremely aggressive with poor prognosis. Here the authors described the clinical pathological and epidemiological characters of triple negative breast carcinomas in a tertiary care hospital in Kerala, India and compare with non-TNBC. Methods: It was a cross sectional comparative study. Clinical, pathological and epidemiological characteristics of 75 cases of TNBC were compared with that of 225 cases of non-TNBC presented in Department of General Surgery, Government medical college, Kozhikode, Kerala, India between a period from March 2014 to October 2015 (20 months). Patients were recruited after obtaining an informed consent. ER, PR, HER-2/neu status were determined by immunohistochemical staining. Data obtained were statistically analyzed using SPSS software. Results: Triple negative breast carcinoma was significantly associated with a younger age (mean age 43.67 years), early age of menarche. Commonly seen in premenopausal age group (78.7%). Patients with the triple-negative carcinoma had relatively large tumors (mean size 4.45cm compared to 3.14cm) and a high rate of node positivity (86.67%). More advanced stage at diagnosis with high grade tumor characteristics. Most common histopathology was invasive ductal carcinoma (98.7%) but no statistical difference was noted with non-TNBC. Conclusions: No significant difference was noted between TNBC and non TNBC on comparing family history, parity, age at 1st child birth, OCP use. The outcome of the disease following treatment was unable to study due to short time frame of the study.